Emotional Labor and Occupational Well-Being: Latent Profile Transition Analysis Approach - Cheung, Francis; Lun, Vivian M. C.; Cheung, Mike W. -L. (Frontiers in Psychology, 2018)
This study used the latent profile transition analysis to analyze whether emotional labor profiles change across time and how these profiles relate to occupational well-being (i.e., job satisfaction, quality of work life, psychological distress, and work–family conflict). A total of 155 full-time Chinese employees completed the questionnaire survey at two time points. Three latent profiles were identified at Time 1 and the same profiles were replicated at Time 2. We determined that the majority of the participants retained the original profiles. Lastly, occupational well-being differed significantly across the identified profiles. The limitations and implications of this study were also provided.